A system and method for exchangeable quantum key distribution - ,, Suryadi; Mohd, Norzaliman; Abdul Khir , Mohd Fared; MD Yusof, Zalhan; Saharudin, Shuhairi (2012)
The present invention provides a system for performing quantum key distribution by securely switching between deterministic and non-deterministic protocol. The system comprising at least one random polarization encoded photon source, at least one optical switch, at least one set of detector for deterministic protocol and a set of detector for non-deterministic protocol and a plurality of electronic logic gates. The said random polarization encoded photon source comprising attenuated pulse laser pumps and optical components for randomly generating polarization photon states while the said optical switch having at least one input port and at least two output ports for switching single photons. The said polarization encoded photon flipper randomly flip polarization state of encoded photon while the said detector for deterministic protocol and detector for non-deterministic protocol having active basis selector and optical components for measuring and discriminating single photon polarization states and the said electronic logic gates comprising electronic controller, timer and analyzer for controlling polarization states of photon to be sent, controlling optical switch based on quantum bit error rate (QBER), controlling polarization encoded photon flipper and controlling active basis selector.